2021
DOI: 10.1186/s12967-020-02693-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of viral load in different specimen types and serum antibody levels of COVID-19 patients

Abstract: Background COVID-19 has caused a global pandemic and the death toll is increasing. However, there is no definitive information regarding the type of clinical specimens that is the best for SARS-CoV-2 detection, the antibody levels in patients with different duration of disease, and the relationship between antibody level and viral load. Methods Nasopharyngeal swabs, anal swabs, saliva, blood, and urine specimens were collected from patients with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 21 publications
5
44
0
1
Order By: Relevance
“… 16 Another study reports anal swab positivity rate of 24.32%, and found two subjects with positive anal swab but negative nasopharyngeal swab. 17 This is similar to our finding, where one patient had positive anal swab result with negative nasopharyngeal swab RT-PCR. This particular patient had two negative nasopharyngeal swab 2 days apart, both negative, but CT scan showed multifocal ground glass opacities and the patient is considered a COVID-19 probable case.…”
Section: Discussionsupporting
confidence: 91%
“… 16 Another study reports anal swab positivity rate of 24.32%, and found two subjects with positive anal swab but negative nasopharyngeal swab. 17 This is similar to our finding, where one patient had positive anal swab result with negative nasopharyngeal swab RT-PCR. This particular patient had two negative nasopharyngeal swab 2 days apart, both negative, but CT scan showed multifocal ground glass opacities and the patient is considered a COVID-19 probable case.…”
Section: Discussionsupporting
confidence: 91%
“…One such method is wastewater-based epidemiology (WBE), which has provided community-scale information on drug use, personal care products, antibiotic resistance, and pathogen circulation ( Choi et al, 2018 ). SARS-CoV-2 is a promising candidate for WBE because its RNA can be detected in stool of infected individuals ( Li et al, 2021 ; Parasa et al, 2020 ), and wastewater surveillance has been shown to provide early detection of population-level increases in occurrence compared to clinical data in some locations ( Ahmed et al, 2021 ; Chavarria-Miró et al, 2021 ; D'Aoust et al, 2021a ; Gerrity et al, 2021 ; Hata and Honda, 2020 ; Kumar et al, 2021 ; Medema et al, 2020 ; Nemudryi et al, 2020 ; Peccia et al, 2020 ; Randazzo et al, 2020b , 2020a , Wong et al, 2021 ; Zhu et al, 2021 ). However, one meta-analysis study reported that SARS-CoV-2 was detected in stool samples from only 41% of infected patients ( Parasa et al, 2020 ), and the viral load has been shown to vary with disease progression ( Benefield et al, 2020 ; Walsh et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Blood samples from non-COVID-19 controls were collected following routine guidelines 18 . The COVID-19 patients were classified as mild (clinical symptoms with no sign of pneumonia), moderate (fever and respiratory symptoms), severe (any of the above criteria and following respiratory distress: ≥ 30 breaths/min; oxygen saturation: ≤ 93% at rest; arterial partial pressure of oxygen/fraction of inspired oxygen: ≤ 300 mmHg; cases with chest imaging that shows lesion progression within 24-48 h > 50%), or critical (any of the above criteria and following respiratory failure, mechanical ventilation, shock, organ failure, and requires ICU care) 19 .…”
mentioning
confidence: 99%